Survey of Taekwondo Sports Equipment Business Management in Semarang City - Prima Ganda; Tri Nurharsono; Heny Setyawati; Puji Purwono (Universitas Majalengka, 2021)
The problem of research “how is the business management of the taekwondo supply in Semarang”. The purpose of this study is to figure out the existence of the taekwondo supply business in Semarang. This study approach uses descriptive method. Techniques of collecting data using purposive sampling. Sources of data in the form of primary data and secondary data. The primary data obtained by interview and observation while secondary data obtained by documentation. Source triangulation and technique triangulation are used to examine the validity of the data. Data analysis obtained by reduction, display data, and conclusion. Based on the research in Semarang, there is a taekwondo supply business that has distributed their goods to several regions in Indonesia. In the operational level, these two companies still use manual methods in the production process and the human resources used are taken from the local community. Basically, these two companies have carried out the management process, while the financial aspects of these two companies differ in capital and objectives. For the information systems, Zao makes better use of them. The company has a fairly good management system because it has fulfilled its four management functions, namely planning, organizing, implementing and controlling. Suggestion the taekwondo supply company in Semarang should develop their marketing management in order to maintain its stability in the field of the taekwondo supply business.